EUTHANASIA IN ISLAMIC VIEWS - Narimisa, Mehran (European Scientific Journal, ESJ, 2014)
We describe two of main sources have been used to find Islamic views towards euthanasia through in this paper as a result of an annual research: First, the Islamic primary source, Holy Koran, which is the most important and reliable source for finding Islamic perspectives, second, religious opinions and decrees (Fatwas) from great Muslim scholars, which are called Mofti Al-AazaminSunni tradition and Ayatollah Al-Ozma in Shiite tradition. These Fatwas are important because of the jurisprudential nature of such bioethical topics in Islamic communities.